Competition for investment and the WTO regulations - Tamulaitis, Donatas (KDI School, 1998)
This work investigates various aspects of competition for FDI, such as theoretical arguments regarding investment incentives, types of investment incentives and the WTO regulations that are related to the investment incentives. It presents the current situation regarding investment incentives in the transition economies of the Central and Eastern Europe in the frame of their compliance with the WTO regulation. The main characteristics of FDI in these countries are also presented. A country providing certain investment incentives might be challenged by the WTO regulations or be subject to the countervailing measures
Thesis(Master) --KDI School:Master of International Economic Policy,1998